Association between Coffee Consumption and Life Expectancy: A Prospective Cohort Study from NHANES 2001-2018 - Guangcan Yan; Xiaoqi Dai; Yun Yan; Jie Yan; Wei Tian; Rui Jiang (Public Health Nutrition)
Abstract